Shadow of Doubt: Scot Harvath #23 - Thor, Brad (New York : Emily Bestler Books, 2024)
"A mysterious cargo plane, flanked by a squadron of Russia's most lethal fighters, has just taken off from a remote airbase. Closely monitored by the United States, no one inside the Pentagon has any idea where it's going or what it's carrying. A high-level Russian defector, a walking vault of secrets that could shatter the West, seeks asylum in Norway. Across the continent, in the heart of Paris, a lone French agent stumbles upon a conspiracy so explosive it could ignite a global firestorm. As alarm bells ring in Washington, the CIA's most lethal weapon, Scot Harvath, is forced to choose between his conscience and his country. You'll be left breathless as Harvath is swept into a whirlwind of double agents, international intrigue, and heart-stopping chases"--.
new book 2024 fall.
Keywords: Harvath, Scot -- (Fictitious character); Intelligence officers -- Fiction; Conspiracy -- Fiction; Defectors; Spy fiction; Spies; -Russia (Federation); FICTION / Thrillers; Norway; Thriller fiction; Spy fiction